From representational to parametric and algorithmic interactions: A panorama of Digital Architectural Design teaching in Latin America. (September 2017) - de Vasconselos, Tássia Borges; Sperling, David
This study focuses on the context of graphic representation technologies and digital design on Architectural teaching in Latin America. From categories proposed by Oxman and Kotnik and through a mapping study framed by a systematic review in CumInCAD database, it is presented a panorama of the state-of-art of the digital design on Architectural teaching in the region, between 2006 and 2015. The results suggest a context of coexistence of representational interaction and parametric interaction, as well as a transition from one to another and the emergence of the first experiments in algorithmic interaction. As this mapping shows an ongoing movement toward Digital Architectural Design in Latin America in the last decade, and points out its dynamics in space in time, it could contribute to strengthen a crowdthinking network on this issue in the region and with other continents.